"FINE ART" IS A CREATIVE PRODUCT FOR CHILDREN IN NEED OF SPECIAL HELP (Conference Zone, 2022)
This is an article about the importance of fine art in working with children with special needs, about creating conditions for their free work. Fine art is a kind of fine art that combines painting, sculpture, graphics; it reflects reality in visual images in its easily recognizable spatial forms.